1984
DOI: 10.1016/0014-4886(84)90098-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differential environments on the cerebral anatomy of rats as a function of previous and subsequent housing conditions

Abstract: After 1 month in enriched or impoverished environments, groups of rats were housed for an additional month in either the same or the opposite environment. The cross-over design allowed us to see whether or not the cerebral effects of differential environments are modified by subsequent housing conditions, and also whether or not such effects might be influenced by previous experience. Differential housing for 1 month was associated with significant alterations in the weight and length of the cerebrum, the thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The cellular effects of EE, which are presumably dependent on molecular changes, include enhanced adult neurogenesis [108,129–133] and synaptic plasticity [134–139]. Specific neuronal cell populations have been shown to be activated by EE [140] and the effects in the brain extend to glia [141–143]. However, a range of other cellular effects have been described, including those impacting on metabolism [144], the immune system [145–148] and the HPA‐axis [47,149–151].…”
Section: Effects Of Ee In Wild‐type Rodents: Insights Into Potential mentioning
confidence: 99%
“…The cellular effects of EE, which are presumably dependent on molecular changes, include enhanced adult neurogenesis [108,129–133] and synaptic plasticity [134–139]. Specific neuronal cell populations have been shown to be activated by EE [140] and the effects in the brain extend to glia [141–143]. However, a range of other cellular effects have been described, including those impacting on metabolism [144], the immune system [145–148] and the HPA‐axis [47,149–151].…”
Section: Effects Of Ee In Wild‐type Rodents: Insights Into Potential mentioning
confidence: 99%
“…The persistence of some of the anatomical changes described above has been examined in reversal experiments in which animals are reared in a complex environment followed by a period of time in standard labora-tory cages. These studies have shown that the increased cortical weight (Katz and Davies, 1984) and dendritic arborization (Camel et al, 1986) observed in rats reared in a complex environment tend to persist. Some of the behavioral consequences of complex housing, such as improved performance on a Hebb-Williams maze, may also persist (Forgays and Read, 1962).…”
Section: Abstract: Motor Learning; Synaptogenesis; Persistence; Cerementioning
confidence: 99%
“…Environmental enrichment or restriction can also affect cerebral size, neuron size, number of glial cells, dendritic branching, spine density, and number of synapses (e.g. Bennett et al ., 1964; Rosenzweig et al ., 1971; Volkmar & Greenough, 1972; West & Greenough, 1972; Globus et al ., 1973; Diamond et al ., 1975; Katz & Davies, 1984), as well as the turnover of several neurotransmitters (Jones et al ., 1992; Myhrer et al ., 1992; Fulford et al ., 1994; Escorihuela et al ., 1995). Little is known concerning the mechanisms that underlie these structural and chemical effects.…”
Section: Introductionmentioning
confidence: 99%